Jango - Nicholson, William (Orlando : Harcourt, 2007)
Seeker, the Wildman, and Morning Star discover that the mysterious warrior sect they had been so desperate to join is not quite what it appears from the outside.
First published: Great Britain : Egmont Books, c2006.
A Junior Library Guild selection
edited hb 2015-06-16
Keywords: Conduct of life -- Juvenile fiction; Faith -- Juvenile fiction; Self-realization -- Juvenile fiction; Conduct of life -- Fiction; Faith -- Fiction; Fantasy; Self-realization -- Fiction; Fantasy fiction